The spiritual brain - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Through discussions with a number of thought leaders in this area, we'll examine the human brain and its predilection for the spiritual. Is it part of our very nature to be concerned with or aware of something beyond ourselves? Or is it part of our culture or any culture for that matter? Is it nurture or nature? Join us as we embark on an adventure into the spiritual brain.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Psychology, Religious; Brain -- Religious aspects